Thomas Dixon and graphic illustration before The Birth of a Nation. Issue 3 (3rd July 2018) - sonstegard, Adam
Abstract: More students of cinematic history know D. W. Griffith's The Birth of a Nation (1915) than Thomas Dixon's novels, upon which Griffith's motion picture is loosely based. Most Dixon students read his novels as prose-only works, but C. D. Williams and Arthur Keller contributed graphic illustrations to the first editions, where theatrical staging underwent novelization, and where literary caricatures invited graphic-arts stereotypes. Recent editions of Dixon's The Clansman (1905), and almost all scholarship responding to Dixon and Griffith, neglect the illustrations, sacrificing graphic arts to cinematic sequels, concealing supremacist imagery, and taking Dixon's novels as prose-only affairs.